Comparison of chemical characteristics and technological parameters in durum wheat based breads enriched with hemp seed flour - Benes Eszter Luca; Szedljak Ildikó (WESSLING Nemzetközi Kutató és Oktató Központ Közhasznú Nonprofit Kft. Budapest, 2019)
Society is getting increasingly food-conscious these days. It can be observed that, in addition to basic cereals such as wheat, rye or maize, the grains of other cereals, pseudocereals and other types of plants that had not been on the market in significant amount have also been appearing. The nutritional values of these plants contribute greatly to the improvement of flour quality. By making various flour blends, we can help produce complete bakery products that are more valuable than the usual ones.Bread is a food whose production uses simple ingredients such as wheat flour, salt, yeast and water. This is why, in many countries, it is the most commonly consumed cereal product that serves as the basis for the diet of many people. Due to its simplicity and widespread consumption, bread is suitable for enrichment with ingredients that provide additional health benefits to consumers. In order to prevent diseases [1], laypeople, as well as professionals consume increasing amounts of foods considered to be healthier than average these days, with the intention, inter alia, of preventing or at least reducing the use of medicinal products obtained in order to maintain or improve their health. Foods with a higher polyphenol content, which may contribute to the prevention of harmful oxidation processes in the human body, may be suitable for this purpose [2]. In the spirit of the above, for the breads prepared by us, flour blends of various compositions were made using durum flour (Triticum durum L.) and hemp seed flour (Cannabis sativa L.). Certain chemical parameters were analyzed in the course of the measurements during the preparation of the breads.
Keywords: Műszaki és technológiai tudományok; Egyéb műszaki tudományok és technológiák; Élelmiszer és italfélék